Glutathione‐S‐transferase‐theta genotypes and the risk of cyclophosphamide toxicity in dogs. (8th July 2018) - Ekena, J.; Wood, E.; Manchester, A.; Chun, R.; Trepanier, L. A.
Abstract : The antineoplastic agent cyclophosphamide (CP) has dose‐limiting side effects including sterile haemorrhagic cystitis (SHC), bone marrow (BM) suppression and gastrointestinal (GI) toxicity in dogs. The metabolites acrolein and phosphoramide that mediate these toxicities are glutathione‐S‐transferase (GST) substrates, and low functioning GST alleles are associated with CP toxicity in humans. The aim of this study was to determine whether variants in 2 canine GST genes, GSTT1 and GSTT5, were over‐represented in dogs that developed CP toxicity. Dogs undergoing pulse or metronomic CP chemotherapy were recruited ( n  = 101) and genotyped for 6 GSTT1 polymorphisms and 1 GSTT5 6‐bp deletion that leads to non‐functional enzyme. Median cumulative CP dosages for dogs with SHC (1350 mg/m 2 ) were significantly higher than for dogs with GI/BM toxicity (871 mg/m 2 ) or no toxicity (991 mg/m 2 ; P  = .0012). Dogs with SHC were more likely to have had metronomic (84.2%, 16 of 19 SHC cases) vs pulse (15.8%, 3 of 19 SHC cases) CP dosing ( P  < .0001). All dogs with BM or GI toxicity ( n  = 30) had pulse chemotherapy. GSTT1 and GSTT5 variant allele frequencies were not significantly different in CP‐treated dogs with SHC or GI/BM toxicity compared to dogs without documented adverse effects. Work is underway to identify which canine GSTs detoxify acrolein and phosphoramide, so that better tools are available to predict the risk of CP toxicity in dogs.